The Natures of War. Issue 1 (21st August 2015) - Gregory, Derek
Abstract: "Nature" is more than a resource bank whose riches can trigger armed conflict and finance its depredations; it is also a medium through which military and paramilitary violence is conducted. The militarisation of nature is part of a dialectic in which earthy, vibrant matter shapes the contours of conflict and leaves its marks on the bodies of soldiers who are both vectors and victims of military violence. Three case studies identify some of the central bio‐physical formations that became entangled with armed conflict in the twentieth century: the mud of the Western Front in the First World War, the deserts of North Africa in the Second World War, and the rainforests of Vietnam. Taken together, these reveal vital connections between the materiality and corporeality of modern war and their continued relevance to its contemporary transformations.